Penegakan Hukum Terhadap Pelaku Penyalahgunaan Narkotika dan Psikotropika - Ruslan Abdul Gani (Universitas Batanghari Jambi, 2008)
Law enforcement toword the narcotics and psychotropica offenders is signed by the ratification of two conventions : single narcotics convention of 1961 and UN convention of 1988 on narcotics which was then followed by UN congress of 1990 on the prevention of crime and the treatment of offenders inHavana,cuba. Since the ratification, law enforcement toword the narcotics affenders inIndonesiaincluding jambi has always been based on the two conventions. However, the implementation always face many problems.